2017
DOI: 10.12968/bjon.2017.26.12.s44
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective wound management: a survey of 1717 nurses

Abstract: Delivering high-quality wound care requires a mix of knowledge and skills, which nurses aim to update by attending educational events such as conferences and study days. This article describes the data obtained from 30 educational study days, which took place across England, Scotland and Wales. It will explore nurses' knowledge in relation to the cost-effectiveness and clinical efficacy of current wound care practices, based on the answers of 1717 delegates that attended the events. It will also outline the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…They conclude that most of the human resource in the health system is used in wound management and recommend that reducing the dressing change frequency in conjunction with a reduction in the number of dressings could lead to a reduction in dressing expenditure 12 . The same opinion has been also expressed by other authors, as they support the view that less frequent changes can have benefits for the patients, as the wound bed is not exposed, the wound healing outcomes are optimized and there is a reduction on dressing expenditure 4,13 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…They conclude that most of the human resource in the health system is used in wound management and recommend that reducing the dressing change frequency in conjunction with a reduction in the number of dressings could lead to a reduction in dressing expenditure 12 . The same opinion has been also expressed by other authors, as they support the view that less frequent changes can have benefits for the patients, as the wound bed is not exposed, the wound healing outcomes are optimized and there is a reduction on dressing expenditure 4,13 .…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the economic burden that arises from frequent dressing changes is not to be overlooked. Costeffective care practices and reduced expenditure on wound dressings are mandatory 4 .…”
Section: Introductionmentioning
confidence: 99%
“…No relevant studies were identified in the grey literature. After excluding duplicates and irrelevant articles, 14 eligible articles remained (Figure 1) 6,[18][19][20][21][22][23][24][25][26][27][28][29][30] . Following screening, secondary sources identified a relevant article which was not identified in the original search as the MESH term "ulcer" was not used in the strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 articles relevant for this scoping review, the majority were quantitative designs (n=11) and the remaining used qualitative designs (n=3), with studies undertaken Of the quantitative studies, nine studies used a cross-sectional descriptive design and two used a quasi-experimental design. The smallest sample was 31 participants 18 and the largest 1,717 participants 19 . Most of these studies had either small samples between 26-50 participants (four studies), or moderate samples between 101-150 participants (five studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation